2020
DOI: 10.1097/jnc.0000000000000196
|View full text |Cite
|
Sign up to set email alerts
|

Reasoned Action Approach Correlates of Physical Activity Among African American Men Living With HIV: A Cross-Sectional Study

Abstract: Physical activity (PA) is associated with a reduced incidence of chronic diseases. However, little is known about the predictors of PA among African American men living with HIV. We report secondary analyses examining the strength of the relationships between the reasoned action approach constructs, attitude, subjective norm, descriptive norm, and self-efficacy and intention to exercise and self-reported adherence to Department of Health and Human Services PA guidelines using baseline data from a trial of a PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…While several studies (Barnidge et al, 2015; Condrasky et al, 2013; Griffith et al, 2016; Ong et al, 2017) exist on adult fruit and vegetable behavior, there is a paucity of studies on fruit and vegetable intake specific to African American men living with HIV. Moreover, a review of the literature identified only one (Kelly et al, 2021) study utilizing the RAA constructs to examine health-promoting behaviors among low-income urban African American men living with HIV. To fill this gap in the literature, the purpose of this study was to examine the utility of the RAA for predicting 5-A-DAYdiet intentions and behavior among older African American men living with HIV.…”
mentioning
confidence: 99%
“…While several studies (Barnidge et al, 2015; Condrasky et al, 2013; Griffith et al, 2016; Ong et al, 2017) exist on adult fruit and vegetable behavior, there is a paucity of studies on fruit and vegetable intake specific to African American men living with HIV. Moreover, a review of the literature identified only one (Kelly et al, 2021) study utilizing the RAA constructs to examine health-promoting behaviors among low-income urban African American men living with HIV. To fill this gap in the literature, the purpose of this study was to examine the utility of the RAA for predicting 5-A-DAYdiet intentions and behavior among older African American men living with HIV.…”
mentioning
confidence: 99%